Time course of estazolam in single-strand hair based on micro-segmental analysis after controlled oral administration - Xu, Duoqi; Ji, Jiaojiao; Xiang, Ping; Yan, Hui; Duan, Gengli; Shen, Min (Frontiers in Chemistry, 2022)
The mechanism of estazolam incorporation into hair was investigated by studying the time course of estazolam along single-strand hair following two oral doses (0 d, 28 d). Estazolam in single hair segments 0.4 mm in length was verified and quantified by ultra-high-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS). The distributions of estazolam within a strand of hair (collected at 12 h, 28 d, and 56 d post-administration) were visualized by micro-segmental analysis. The highest estazolam concentration (1.5 to 9.9 pg/mm) was detected in the hair bulb region (S1), and it then decreased through the hair shaft to the distal end, with a small fluctuation (0.3 to 3 pg/mm) near the junction of the hair roots and shafts (S4–S7) 12 h after drug intake. These findings suggested that the incorporation of estazolam occurred in two regions, mainly in the hair bulb and to a lesser extent in the upper dermis zone. Models using internal temporal markers (TIMs) and temporal intervals (TIs) were constructed to estimate the day of estazolam ingestion. The estimation accuracy was within an average error of 1.7 mm and 3.0 mm between the calculated and actual positions, based on the TIMs and TIs 56 d after estazolam intake. These findings can help in further elucidation of the drug incorporation mechanism, which is crucial for interpreting hair analysis results used to reveal individual drug-use history.